Pengembangan E-Modul Berbasis Flipbook untuk Meningkatkan Minat Belajar Siswa Pada Materi Cerita Fantasi Kelas VII SMP Negeri 1 Botomuzoi - Fany Erlinawati Hulu; Putri Harefa; David Angelus Emanuel Laia; Trisman Harefa (Departement of Mathematics Education, 2023)
This research was conductedto increase student interest in fantasy story material for class VII by developing flipbook-based e-module learning media. The objectives in conducting this research were: to determine student responses to flipbook-based e-modules on fantasy story text material for class VII N 1 Botomuzoi and to determine the feasibility of flipbook-based e-modules on fantasy story material that has been developed. The method used in this study is Research and Development (R&D) with the development model used is the ADDIE development model flow developed by Dick and Carry (1996) with the stages of Analysis, Design, Development, Implementation, and Evaluation. To obtain data from this study, the researcher used a material expert validation questionnaire, media and student response questionnaires. This development research resulted in the feasibility of the product being developed, validation tests were carried out involving material expert teachers with an average score of 93.06%, media experts with an average score of 92.38% and trials on students with an average score of 88, 75% with very valid and proper criteria to use.